Recent High-Resolution Structures of Amyloids Involved in Neurodegenerative Diseases - Diaz-Espinoza, Rodrigo (Frontiers in Aging Neuroscience, 2021)
Amyloids are highly ordered aggregates composed of proteins or peptides. They are involved in several pathologies, including hallmark neurodegenerative disorders such as Alzheimer’s (AD) and Parkinson’s (PD). Individuals affected by these diseases accumulate in their brains amyloids inclusions composed of misfolded forms of a peptide (A) and a protein (Tau) in AD and -synuclein protein (-Sn) in PD. Tau and -Sn aggregates are also present in other neurodegenerative diseases. The insoluble nature and heterogeneity of amyloids have hampered their study at the molecular level. However, the use of solid state NMR and Cryogenic-electron microscopy along with fine-tuned modulation of the aggregation in vitro and improved isolation methods of brain-derived amyloids has allowed the elucidation of these elusive conformations at high resolution. In this work, we review the latest progress on the recent amyloid structures reported for A, Tau and -Sn. The two-fold symmetry emerges as a convergent feature in the tridimensional arrangement of the protofilaments in the fibrillary structure of these pathological amyloids, with many of them exhibiting a Greek-key topology as part of their overall architecture. These specific features can serve as novel guides to seek potential molecular targets in drug design efforts.